Word and object recognition during reading acquisition: MEG evidence - Sendy Caffarra; Clara D. Martin; Mikel Lizarazu; Marie Lallier; Asier Zarraga; Nicola Molinaro; Manuel Carreiras (Developmental Cognitive Neuroscience, 2017)
Studies on adults suggest that reading-induced brain changes might not be limited to linguistic processes. It is still unclear whether these results can be generalized to reading development. The present study shows to which extent neural responses to verbal and nonverbal stimuli are reorganized while children learn to read. MEG data of thirty Basque children (4–8y) were collected while they were presented with written words, spoken words and visual objects. The evoked fields elicited by the experimental stimuli were compared to their scrambled counterparts. Visual words elicited left posterior (200–300 ms) and temporal activations (400–800 ms). The size of these effects increased as reading performance improved, suggesting a reorganization of children’s visual word responses. Spoken words elicited greater left temporal responses relative to scrambles (300–700 ms). No evidence for the influence of reading expertise was observed. Brain responses to objects were greater than to scrambles in bilateral posterior regions (200–500 ms). There was a greater left hemisphere involvement as reading errors decreased, suggesting a strengthened verbal decoding of visual configurations with reading acquisition. The present results reveal that learning to read not only influences written word processing, but also affects visual object recognition, suggesting a non-language specific impact of reading on children’s neural mechanisms. Keywords: MEG, Reading acquisition, Visual word recognition, Speech processing, Object recognition